Research on the camel: A look at the past and some pointers for the future - Wilson, R.T. (1982)
Reviews research conducted on the one humped camel, camelus dromedarius, in the tropics. Shows normal limits of distribution of camels in Africa; presents a chronological analysis of literature references for specific fields of research, distribution of published references between major subjects, published work on the camel from 1850 to 1980, and literature sources by country of origin and nationality of researchers with an interest index for related countries of areas.